Intermolecular interactions in crystalline 1-(adamantane-1-carbonyl)-3-substituted thioureas with Hirshfeld surface analysis. Issue 39 (17th September 2015) - Saeed, Aamer; Bolte, Michael; Erben, Mauricio F.; Pérez, Hiram
Abstract : The 1-acyl thiourea synthon is characterized through a complete Hirshfeld surface analysis for a series of six closely related 1-(adamantane-1-carbonyl) thioureas. Abstract : The conformationally congested species 1-(adamantane-1-carbonyl)-3-(2, 4, 6-trimethylphenyl)thiourea has been prepared and fully characterized by elemental analyses, FTIR, 1 H NMR, 13 C NMR and mass spectrometry. Its crystal structure was determined by single-crystal X-ray diffraction. The dihedral angle between the plane of the 2, 4, 6-trimethylphenyl group and the plane of the thiourea fragment was optimized by theoretical calculations applying the B3LYP/6-311++G(d, p) level for the purpose of investigating the conformational effects on the stabilization of the crystal packing. A detailed analysis of the intermolecular interactions in a series of six closely related phenylthiourea species bearing the 1-(adamantane-1-carbonyl) group has been performed based on the Hirshfeld surfaces and their associated two-dimensional fingerprint plots. The relative contributions of the main intermolecular contacts as well as the enrichment ratios derived from the Hirshfeld surface analysis establish the 1-acyl thiourea synthon to be a widespread contributor.